Management Aspects of the Quality of Auditing Services through the Prism of Philosophical and Economic Concepts - Balan, Igor; Lupu, Constantin; Moldovan, Mirela (The Journal of Accounting and Management, 2024)
Currently, the problems that arise in the audit activity not only in individual countries, but also in the world as a whole, are of an institutional nature and are associated with the inefficiency of the functioning of the audit institution as a whole. The most important function of the audit institution is to establish the quality of published financial information of socially significant economic entities, and one of the possible dysfunctions is to confirm poor-quality financial information on the performance of such economic entities. The elimination and prevention of this dysfunction in the future is possible only with the introduction of an effective mechanism for ensuring the quality of the audit. In this paper, the authors reveal some aspects of quality, as one of the most ancient categories, through the prism of philosophical and economic concepts.